Adheer Vyavasthapak - Vieira, Walter (Sage Publications Pvt. Ltd, 2017)
The rules of the corporate world are now dynamic like never before. For managers, the marathon race, starting at the bottom of the pyramid and working their way upto the top in 20-30 years, is no longer a fundamental tr.